N BROMO METHYL PHTHALIMI DEASA REAGENT FOR THE CHARACTERIZATION OF ALCOHOLS AND PHENOLS - MANCERA, O; LEMBERGER, O (UNIVERSIDAD NACIONAL AUTONOMA DE MEXICO. INSTITUTO DE QUIMICA, CD. MEXICO, DF, MEX, 1951)
The use of N-bromomethylphthalimide as a reagent for the characterization of alcohols and phenols has been suggested and its use exemplified by the preparation of a number of derivatives.
J REPROD FERTIL
Keywords: N BROMO METHYL PHTHALIMI, DEASA REAGENT, CHARACTERIZATION, ALCOHOLS, PHENOLS; QUIMICA; QUIMICA ORGANICA; MECANISMOS DE REACCION